THE USE OF PUPPET STORY FOR BASIC ENGLISH INTRODUCTION TO 1ST GRADE ELEMENTARY SCHOOL STUDENTS - Zahara, Meutia; Nisa, Rahmatun; Helmanda, Cut Mawar (Universitas Muhammadiyah Aceh, 2022)
This community service activity had been held for 1st grade elementary school of SD Muhammadiyah Banda Aceh during June 2022. The use of puppet and storytelling in introducing basic English is an interesting and fun activity for children. This activity aimed to make the participants able to understand basic English quickly which can be used as a stepping stone to understand English daily. The methodology used was the lecture method using puppet in the form of cards that have been attached to ice cream sticks and colored. The materials provided were alphabets, numbers and colors, then followed by storytelling using other puppets entitled The bear and friends. The results obtained that the participants were very enthusiastic and able to catch the material quickly, this can be seen when the participants could answer all the questions about the materials provided.Keyword: Puppet story, basic English, community service